PROTECTIVE EFFECTS OF QUERCETIN ON THE HEALING PROCESS OF EXPERIMENTAL COLONIC ANASTOMOSIS IN RATS - SELMA ERDOGAN DUZCU; HAYRETTIN OZTURK; AYHAN CETINKAYA; OZGUR MEHMET YIS; HULYA OZTURK (Journal of Animal and Plant Sciences, 2023)
The protective effects of quercetin on colonic anastomosis in rats were investigated by mechanical, biochemical and histopathological parameters. Twenty-one male, Sprague–Dawley rats (240–250 g) were used in this study.Group 1, (Sham-control): The abdominal cavity was entered and after the cecum and colon were exposed, they were reinserted into the abdomen without any procedure. Group 2 (Colon anastomosis+untreated): The abdominal cavity was entered and, 2 cm colon was resected from the distal cecum and the colon was anastomosised end-to-end. Group 3 (Colon anastomosis + Quercetin treatment): In addition to the procedure applied in group 2 rats, after colon anastomosis, quercetin was administered at a dose of 50mg/kg by oral gavage for 7 days. The results were evaluated with mechanical, biochemical and histopathological parameters. In the group 2, anastomotic burst pressures on the eighth postoperative day were decreased compared to the group 1. The burst pressure measurements were significantly higher in the group 3 compared to the group 2. MPO and MDA values in the group 2 showed a significant increase when compared to the group 1. However, these values were significantly decreased in group 3 rats compared to group 2 rats, and SOD values were increased. When the histopathological parameters in the group 2 were compared with the groups 1 and 3, significant changes were found on Colonic anastomosis, anastomotic healing, breaking strength, reactive oxygen species, quercetin, rat the negative side. On the other hand, when quercetin treatment group was compared with group 2, a statistically decrease in inflammatory parameters and mucosal and muscular damage and increased angiogenesis were detected. The results of our study showed that quercetin treatment has positive effects on the healing of colon anastomosis and these effects are based on its antioxidant and anti-inflammatory properties.
Keywords: Colonic anastomosis; anastomotic healing; breaking strength; reactive oxygen species; quercetin; rat